Let’s Work Together — Occupational Factors and Their Correlates to Prison Climate and Inmates’ Attitudes Towards Treatment - Sauter, Julia; Vogel, Joanna; Seewald, Katharina; Hausam, Joscha; Dahle, Klaus-Peter (Frontiers in Psychiatry, 2019)
The role of psychosocial and structural occupational factors in mental health service provision has broadly been researched. However, less is known about the influence of employees’ occupational factors on inmates in correctional treatment settings that mostly seek to apply a milieu-therapeutic approach. Therefore, the present study investigated the relationships between occupational factors (job satisfaction, self-efficacy, and the functionality of the organizational structure) and prison climate, the number of staff members’ sick days as well as inmates’ treatment motivation. Employees (n = 76) of three different correctional treatment units in Berlin, Germany, rated several occupational factors as well as prison climate. At the same time, treatment motivation of n = 232 inmates was assessed. Results showed that higher ratings of prison climate were associated with higher levels of team climate, job satisfaction and the functionality of the organizational structure, but not with self-efficacy and sick days. There was no significant relationship between occupational factors and the perceived safety on the treatment unit. Inmates’ treatment motivation was correlated with all aggregated occupational factors and with average sick days of staff members. Outcomes of this study strongly emphasize the importance of a positive social climate in correctional treatment units for occupational factors of prison staff but also positive treatment outcomes for inmates. Also, in the light of these results, consequences for daily work routine and organizational structure of prisons are discussed.